2016
DOI: 10.4269/ajtmh.16-0221
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Transmission Pattern of Hepatitis A: An Experience from a Hepatitis A Outbreak Caused by Two Cocirculating Genotypes in Sri Lanka

Abstract: Abstract. Sri Lanka is one of the intermediate-endemic areas for hepatitis A virus (HAV), and concerns exist about the increasing HAV-susceptible population. In fact, Sri Lanka recorded a large hepatitis outbreak, possibly hepatitis A, around the end of the Sri Lankan war. It included more than 14,000 patients consisting of local residents, internally displaced personnel, and military personnel in the main combat zone. The outbreak had slowed down by October 2009; however, acute viral hepatitis continued to oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Typical clinical presentation, including adolescent and adult cases, was reported in detail in five studies, from India [18, 30, 31], Pakistan [32] and Sri Lanka [33]. All of these studies reported patients with jaundice (80–100%), abdominal pain (26–82%) and fever (45–91%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical clinical presentation, including adolescent and adult cases, was reported in detail in five studies, from India [18, 30, 31], Pakistan [32] and Sri Lanka [33]. All of these studies reported patients with jaundice (80–100%), abdominal pain (26–82%) and fever (45–91%).…”
Section: Resultsmentioning
confidence: 99%
“…Several HAV outbreaks were reported across India between 2004 and 2017 [4, 31, 38–43] as well as one in Sri Lanka in 2009–2010 [33, 44] (Table S2). It was noted that men were more affected as were adolescents and young adults (16–30 years, 142 cases) [42, 43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), the derived strains were different. However, it is known that the virulence of HAV is similar between different genotypes of strains (21,22). Therefore, the virulence of the strain between the 1999-2000 and 2017-2018 groups was considered to be similar.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, Sri Lanka experiences outbreaks of hepatitis A, which has become a significant health problem. 8 Random blood sampling in healthy individuals living in Colombo in 1975 showed prevalence of hepatitis A immunoglobulin G to be 76.9%; age-specific analysis indicated that infections were acquired during child-hood. 9 In 2001, a study conducted in Lady Ridgeway Children’s Hospital in Colombo among 288 children showed only 11.6% seroprevalence of hepatitis A antibody among children aged less than 10 years, and 78% of them were from families earning less than 10,000 rupees a month.…”
Section: Hepatitis Amentioning
confidence: 99%